LAW AND DEVELOPMENT IN THE CONTEXT OF THE CERRADO (CIPEEX, 2022)
THE PRESENT RESEARCH HAS AS ITS MAIN OBJECTIVE TO ANALYZE THE CONCEPT OF LAW, AND DEVELOPMENT IN THE CONTEXT OF THE CERRADO, SINCE IT IS LOCATED IN THE CENTRAL REGION OF BRAZIL, AND 12 OF ITS 27 FEDERATIVE UNITS ARE CONTEMPLATED WITH THE BIOME. LEGISLATION MUST ACCOMPANY SOCIAL TRANSFORMATIONS AND ENSURE PROTECTION FOR INDIVIDUALS AND THE COMMUNITY IN A POSITIVE WAY, HOWEVER, ALTHOUGH THE CERRADO IS THREATENED WITH EXTINCTION DUE TO THE INTENSE DEVASTATION RESULTING FROM ECONOMIC ACTIVITY SINCE THE 1940S, BRAZILIAN LEGISLATORS HAVE NOT APPRECIATED SINCE 1995, THE VARIOUS PROPOSALS FOR CONSTITUTIONAL AMENDMENTS, WHICH ADDRESS THE INCLUSION OF CERRADO IN THE LIST OF BIOMES CONSIDERED NATIONAL HERITAGE; SUCH A LEGISLATIVE GAP POINTS TO THE SERIOUSNESS THAT THE ISSUE MUST BE TREATED, SUCH IS THE URGENCY OF THE ISSUE. IT WAS FOUND THAT THE ABSENCE OF THE EXPLICIT PROVISION OF THE CERRADO IN THE FEDERAL CONSTITUTION OF 1988, MAKES IT NECESSARY TO INTERPRET ARTICLE 225 OF THE 1988 CONSTITUTION EXTENSIVELY, CONSIDERING IN A GENERAL WAY THE LEGISLATOR'S INTENTION OF ENVIRONMENTAL PROTECTION FOR ALL NATIONAL BIOMES. HOWEVER, ALTHOUGH THERE IS THIS INTERPRETATIVE AND INCLUSIVE POSSIBILITY OF THE CERRADO IN THE FEDERAL CONSTITUTION OF 1988, IT DOES NOT CANCEL THE AGENDA THAT THE CERRADO MUST BE CONFIGURED AMONG THE LIST OF NATIONAL HERITAGE LITERALLY AND EXPLICITLY CONSTITUTIONALLY, DUE TO ITS ECOSYSTEM IMPORTANCE. ITS OBJECTIVE IS THE STUDY AND REFLECTION ON THE EFFECTIVENESS OF THE PRECAUTION WITH THE CURRENT SITUATION IN THE CERRADO CONTEXT AND ALSO, TO OUTLINE THE OBJECTIVES SO THAT IT COULD BE ELUCIDATED, THE RESEARCH METHODOLOGY USED WILL BE THE ANALYTICAL METHOD TO CONCEPTUALIZE THE SITUATION OF THE THICK. IT IS NOTEWORTHY THAT THE RESEARCH WILL DISCUSS THE CONSTITUTIONAL LEGISLATIVE GAP ON THE CERRADO, SHOWING HOW IT NEGATIVELY IMPACTS A BIOME IN A RAPID PROCESS OF DEVASTATION. IT IS ALSO PROPOSED THE INTERDISCIPLINARY STUDY OF SUSTAINABILITY IN THE LIGHT OF DEEP ECOLOGY AND ENRIQUE LEFF'S PROPOSAL OF ENVIRONMENTAL RATIONALITY, SEEKING AN ETHICAL RETHINK ABOUT THE RELATIONSHIP BETWEEN HUMAN BEINGS AND NATURE. IT IS CONCLUDED THAT, WITH THE RESEARCH, THE STUDY OF THE PROCESS OF INCLUSION OF THE CERRADO BIOME IN §4 OF ARTICLE 225 OF THE FEDERAL CONSTITUTION OF 1988 CLARITY, AND DESCRIBE HOW THE LEGISLATIVE ATTEMPTS TO INCLUDE THE CERRADO IN THE LIST OF BIOMES CONSIDERED HERITAGE HAVE BEEN NATIONAL.
Keywords: brasil cerrado; environmental law; sustainable development